HUBUNGAN POLA ASUH ORANGTUA TERHADAP SIKAP ANTI SOSIAL PADA REMAJA SERTA IMPLIKASI BAGI PROGRAM BIMBINGAN DAN KONSELING - Oktanovia, Risa; Khairun, Deasy Yunika; Wibowo, Bangun Yoga (JIEGC Journal of Islamic Education Guidance and Counselling, 2022)
This study aims to determine the relationship between parenting and antisocial attitudes of students. The approach used in this research is a quantitative approach with the type of correlational research. The population in this study was class VIII students at SMP Negeri 12 Kota Serang with 144 subjects out of 226 students. This research uses random sampling technique in determining the sample. The data collection method in this study used a parenting and antisocial scale that had been validated by expert lecturers and processed the data using SPSS for windows 24.0 series. It is known to have the results of a simple correlation analysis (r) it is found that the correlation between the relationship between parenting and antisocial parenting is -0.228 with a significance of 0.006 <0.05. This shows that there is a relationship between parenting and antisocial parenting. While the direction of the relationship is negative because the r value is negative, which can be seen from the Pearson correlations, which is negative, meaning the higher the influence of parenting, the lower the level of antisocial attitudes experienced by students. The value of determination (R square) of 0.052 can be interpreted that social support provides an effective contribution of 5.2% towards antisocial attitudes, meaning that there are still 94.8% caused by other variables not discussed in this study.